Prediksi Erosi di Wilayah Jawa Timur - Rhoshandhayani Koesiyanto Taslim; Marga Mandala; Indarto Indarto (School of Postgraduate Studies, Diponegoro Univer, 2019)
Erosion is an event of eroding soil that occurs naturally. However, human activities that change land use from natural (forestry, plantation, rural areas) to urban features can alter the erosion processes. Rapid calculation of erosion level for the wide area is necessary for the management and conservation planning. This research aims to analyze the erosion level in East Java area using USLE (Universal Soil Loss Equation) and GIS. The erosivity factor (R) is calculated from rainfall data. Vegetation factor (C) and the conservation factor (P) estimated from land use map. The length and slope factor (LS) are calculated from the ASTER GDEM2, and the erodibility factor (K) is obtained from interpretation of soil map. Furthermore, all factors were analysed to calculate erosion rate. The result shows that the average erosion rate in East Java regions is 10,30 tons/ha/year. The result also show that 78,71% area of East Java is classified as very low erosion rate (0-15 tons/ha/year); 10,75% classified as low erosion rate (15-60 tons/ha/year); 6,39% classified as moderate erosion rate (60-180 tons/ha/year); and 2,83% is severe type (180-480 tons/ha/year). Only 1,31% from the total area is classified as very severe erosion rate (>480 tons/ha/year). The result also shows that USLE can be used to facilitate rapid erosion prediction for wide area.